Effect of childhood trauma on adult depression and neuroendocrine function: sex-specific moderation by CRH receptor 1 gene - Christine Heim (2009)
Variations of the corticotropin-releasing hormone receptor 1 (CRHR1) gene appear to moderate the development of depression after childhood trauma. Depression more frequently affects women than men. We examined sex differences in the effects of the CRHR1 gene on the relationship between childhood trauma and adult depression. We recruited 1,063 subjects from the waiting rooms of a public urban hospital. Childhood trauma exposure and symptoms of depression were assessed using dimensional rating scales. Subjects were genotyped for rs110402 within the CRHR1 gene. An independent sample of 78 subjects underwent clinical assessment, genotyping, and a dexamethasone/CRH test. The age range at recruitment was 18-77 years and 18-45, for the two studies respectively. In the hospital sample, the protective effect of the rs110402 A-allele against developing depression after childhood trauma was observed in men (N = 424), but not in women (N = 635). In the second sample, the rs110402 A-allele was associated with decreased cortisol response in the dexamethasone/CRH test only in men. In A-allele carriers with childhood trauma exposure women exhibited increased cortisol response compared men; there were no sex differences in A-allele carriers without trauma exposure. This effect may, however, not be related to gender differences per se, but to differences in the type of experienced abuse between men and women. CRHR x environment interactions in the hospital sample were observed with exposure to physical, but not sexual or emotional abuse. Physical abuse was the most common type of abuse in men in this cohort, while sexual abuse was most commonly suffered by women. Our results suggest that the CRHR1 gene may only moderate the effects of specific types of childhood trauma on depression. Gender differences in environmental exposures could thus be reflected in sex-specific CRHR1 x child abuse interactions.